Physical Education Learning Model to Improve Basic Running Movements of Elementary School Students: Systematic Literature Review - Toni Latifi; Mashud (S&Co Publishing, 2026)
This study aims to examine effective Physical Education learning models in improving basic running movements in elementary school students through a Systematic Literature Review (SLR) approach. The background of the study is based on the continued dominance of conventional Physical Education (PJOK) learning, which is less than optimal in developing students' basic movement skills. The research method used SLR with the PICO procedure and PRISMA flow. Articles were obtained through the Google Scholar database with a publication range of 2021–2025. The selection process was carried out using inclusion and exclusion criteria until seven relevant articles were obtained for qualitative analysis. The results of the study indicate that game-based learning models, especially traditional games and modified games, consistently improve students' basic running movement abilities. In addition to improving psychomotor aspects, this model also has a positive impact on student activity, motivation, and participation in learning. The discussion links these findings to motor development theories and active learning that emphasize direct learning experiences. It is concluded that game-based PJOK learning is an effective, contextual approach, and appropriate to the characteristics of MI/SD students, although further research with a stronger design is still needed to expand the validity of the findings.